O efeito da compressão por ataduras elásticas na dor e função em indivíduos com osteoartrite de joelho: ensaio clínico controlado randomizado - Ferrari, Angelica Viana (2024)
Compression is widely used in combination with cryotherapy and other non-pharmacological physical agents to control musculoskeletal pain. However, there is still a lack of evidence regarding its possible effects on modulating this type of pain. This study evaluated the effect of compression by elastic bandages on pain and physical function in individuals with knee osteoarthritis (KOA). Methods: Randomized, three-arm, prospectively registered trial, blinded assessors, allocation concealment, and intention-to-treat analysis. Participants: Ninety individuals with KOA, of both sexes, between 40 and 75 years of age, with current pain > 4 cm on the 10 cm visual analogue scale (VAS). Intervention: For four days, the experimental group used an elastic bandage compressed on the painful knee for 20 minutes; the sham group used elastic bandages without compression; and the control group did not use a dressing. Outcome measures: Primary outcomes were visual analogue scale (VAS) pain and pain subscale of the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Secondary outcomes included self-reported (WOMAC) and objective physical function (step tests; 30-second sit-to-stand test; 40-m brisk walk test) and global change rating scale. Measurements were taken at day 1, day 6 and 12 weeks. Results: Immediately after the intervention, the mean difference between the groups in the stiffness, function and total index subscales were statistically significant, favoring the experimental group and the sham group, compared to the control, but without reaching the minimum clinically important difference (MCID). At the same time, the experimental group reached the MCID in the pain variable after the 9-step test when compared to the control group. For the other times and comparisons there were no significant results. Conclusion: The application of elastic bandage compression to the knee of individuals with KOA was not superior to a sham intervention and a negative control in reducing pain and improving physical function. Trial Registration: NCT04724902.